A synthetic hybrid promoter for D-xylonate production at low pH in the tolerant yeast Candida glycerinogenes. Issue 6 (2nd November 2017) - Ji, Hao; Lu, Xinyao; Zong, Hong; Zhuge, Bin
ABSTRACT: The tolerant yeast Candida glycerinogenes, with high D-xylonate and low-pH tolerances, was used as the host for D-xylonate production at low pH in this study. A low-pH inducible promoter, pGUKd, was engineered using the core promoter of the glyceraldehyde-3-phosphate dehydrogenase gene (pGAP) combined with the upstream activating sequence of the promoter of the guanylate kinase gene (pGUK1) that had substituted pH-responsive TF binding sites. The recombinant cells that expressed GFP from the hybrid promoter pGUKd displayed dramatically increased fluorescence intensity at pH 2.5, thus verifying that pGUKd is a low-pH inducible promoter. The promoter pGUKd was then used to express the D-xylose dehydrogenase gene xylB, resulting in increased expression levels of xyl B at low pH. The recombinant protein exhibited higher specific activities under lower pH conditions and produced 38 g/l D-xylonate at pH 2.5. This rate is much higher than that produced by fermentation at pH 5.5. These results suggest that the novel hybrid promoter pGUKd functions to direct the production of D-xylonate at low pH, and we provide a candidate genetic tool for the stress tolerant yeast C. glycerinogenes .